Method for Diagnostics of Carp Fish Diplostomosis During Veterinary and Sanitary Examination - Marchenko , Alexander; Mironova, Anna; Duletov, Evgeny; Choporova, Natalia; Kravchenko, Alexander (KnE Life Sciences, 2021)
Diplostomosis is an invasive disease of carp fish that can cause significant damage to the fish farm. It is widely distributed in Russia, Kazakhstan, Ukraine and Belarus. Sexually mature individuals parasitize the intestines of fish-eating birds of the genus Laridae. The intermediate host is freshwater fish and mollusks of the genus Lymnaea. The disease cycle is represented by several migrations of the parasite from the reservoir to the intermediate hosts, followed by ingestion. Fry and fish with a low immune status are most susceptible to this disease. When introduced into the body, trematodes can inoculate fish with various pathogenic and conditionally pathogenic microflora inherent in the habitat, which can complicate the production of high-quality products that are safe for both humans and animals. Therefore, the implementation of our patented “Method for assessing the quality of meat of fish infected with diplostomosis” during the veterinary and sanitary examination is important. The invention involves diagnostic measures, namely, to determine the quality of fish meat, which were carried out in this study. The method consisted of a step-by-step study of the pathogen obtained by destroying the integrity of the vitreous body and sowing exudate by collecting the material with a Pasteur pipette with transfer to the MPA. These were kept in a certain temperature regime for at least 48 hours. The researchers examined the plates with the inoculations and described the morphology of the resulting colonies, with preliminary staining of the smears according to Romanovsky-Giemsa. The colonies were counted using the Goryaev camera. The method used helped to detect the parasitic disease together with the bacteriological purity of the fish, which makes it possible to issue a correct veterinary and sanitary assessment for a given invasion. The data were processed statistically; a correlation relationship between the intensity of invasion and the level of the bacteriological flora of fish products was established. The most significant was the relationship of contamination with bacteria of the E. coli group and of the genus Pseudomonas and Staphylococcus. The obtained value of the KMAFAMnM index exceeded the indicator of healthy fish. Keywords: diplostomosis, post-diplostomosis, methods, identification, parasitology, microbiology